Nano-MgO Synthesis and Characterization using MgCl2 via Precipitation Method - Rizal, Moh Najib; Nurhayati, Ervin; Tangahu, Bieby Voijant; Bhakti, Lingga Manunggal (Universitas Andalas, 2025)
This study examined the synthesis of nano-MgO via a precipitation method involving technical-grade magnesium chloride (MgCl2) as the starting material and ammonium hydroxide (NH4OH) as the precipitating agent. The objective of this study was to fine-tune the synthesis procedure by altering the concentration of NH4OH (0.5% and 1%) and to assess the properties of the resulting nanoparticles in terms of their suitability for applications. The properties of the synthesized nano-MgO were identified using X-ray fluorescence (XRF), X-ray diffraction (XRD), iodine number adsorption, and Brunauer-Emmett-Teller (BET) analysis to evaluate the oxides content, minerals formed and the crystallinity, adsorption capacity, surface area, and porosity. The findings show that, compared to 1%, a concentration of 0.5% NH4OH produced a superior MgO. A nano-MgO with 87.1% purities (of dominantly periclase phase), with an average crystallite grain size of 11.383 nm was formed. The iodine adsorption capacity of 243.01 mg/g, BET surface area of 43.4298 m2/g, and average pore diameter of 9.0002 nm were achieved, indicating formation of nanoporous structure, well-suited for a wide range of industrial use. Whereas when using 1% NH4OH, the purity only reached 83% (of the same dominant phase) with an average crystallite grain size of 11.691 nm, and iodine number of 197.98 mg/g. This research findings indicate that the precipitation method using 0.5% NH4OH is the effective method for producing high-quality nano-MgO from technical grade precursor with improved adsorption capabilities and suitability for large-scale fabrication. Keywords: Nano-MgO, Precipitation, Characterization